Um olhar linguístico-discursivo sobre o Edital PRG/SISU 1ª edição de 2019 da Universidade Federal da Paraíba – UFPB - Varela, Angela Brasil Claudino (2021)
Reflecting on affirmative action means thinking about the mainstay of the law as a basic guarantee of social equality. Faced with the neutrality of the Major State in resolving the ethnic-racial and social inequalities that affect certain socially downgraded and excluded citizens, public policies on affirmative action develop as instruments to ensure an essential transformation that restores equality at the heart of society. The general objective of this research is to analyze the Public Call Notice Edital PRG/UFPB do SiSU 1ª edição/2019 – Sistema de Seleção Unificada, do Ministério da Educação – MEC, with the purpose of identifying the linguistic and discursive weaknesses that lead to cases of fraud in the system of access to the graduation courses of the Federal University of Paraíba. With a linguistic-discursive look at the discourses that are constructed and legitimated at the time of the textual production of the Tendering Instrument instituted and written within the sphere of the Office of the Pro-Rectory of Graduate Studies of this institution, we analyzed the corpus. The emphasis of the analysis of the chosen corpus emerges as a mandatory contribution, in the face of the discursive genre covered. The genre of the Public Call Notice is different from other discursive genres, given the formality, the structure and official status, especially due to its informative and institutional nature. In light of the analysis of the French discourse analysis carried out by Dominique Maingueneau (1997, 2000, 2002, 2005a, 2005b, 2008, 2008a, 2008b, 2008c, 2010, 2015), we seek to understand the meaning of the discourses in the chosen corpus, stating the principles of scenography and ethos. We mapped the linguistic and discursive fragments within the competence of the UFPB’s Public Call Notice writer, attempting to guide them in the textual production of the language based on the instrument used as a perpetuated voice in UFPB’s affirmative action policy, as an institutional source of higher education. This study is built according to a qualitative approach with quantitative contributions in the use of bibliographical and documentar research for its discussion. This research is focused on analyzing the fragments of the UFPB’s Public Call Notice, being of great relevance and institutional contribution, because there is the offer of vacancies of admission to the graduation courses of this institution. To identify the elements of the scenography and the ethos in the discursive construction of this formal mechanism, which determines the access to higher education through the quota system in SiSU and to categorize the linguistic and discursive weaknesses in the context of production that lead to fraud in the regulatory system, especially in the scope of UFPB in 2019, help to obtain satisfactory results in the elaboration of future linguistic instruments created with the main purpose of normativity and institutionality of the quota reservation policy as greater guarantee.